2020
DOI: 10.1177/0743915620922873
|View full text |Cite
|
Sign up to set email alerts
|

How Product Type and Organic Label Structure Combine to Influence Consumers’ Evaluations of Organic Foods

Abstract: This research finds that how a firm conveys a food’s organic nature through an organic label impacts consumers’ evaluation of that food. Consistent with previous research, adding organic labels to foods is detrimental to evaluations of vice (but not virtue) foods, but simple changes to the structure of the organic label attenuate the negative effect of such labels on evaluations of vice foods. Specifically, whereas product-level organic labels (e.g., “organic burrito”) result in lower evaluations of vice foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Doom and Verhoef (van Doorn and Verhoef, 2011) found that consumers were willing to pay a premium for organic labeling of autos and were unwilling to pay a premium for organic labeling of indulgences due to perceived quality issues. Consistent with previous findings, Parker et al . (2021) found that organic labeling in food products was detrimental to the evaluation of vice products but that simply changing the organic labeling construct attenuated the negative evaluation of indulgences.…”
Section: Literature Reviewsupporting
confidence: 93%
“…Doom and Verhoef (van Doorn and Verhoef, 2011) found that consumers were willing to pay a premium for organic labeling of autos and were unwilling to pay a premium for organic labeling of indulgences due to perceived quality issues. Consistent with previous findings, Parker et al . (2021) found that organic labeling in food products was detrimental to the evaluation of vice products but that simply changing the organic labeling construct attenuated the negative evaluation of indulgences.…”
Section: Literature Reviewsupporting
confidence: 93%
“…Karahan Uysal et al [71]; Janssen and Hamm [72]; Richetin et al [73]; Meyerding and Merz [74]; Yin et al [75]; Parker et al [76], Study 1a; Gaylord et al [77]) compared products with several organic label variants, rather than products with no (or a conventional) label and those with an organic label; i.e., they examined whether there is a difference in consumers' evaluation as a result of the type of label on the product, not the effect of the organic label. The examination by Mather et al [78], Gifford and Bernard [62], and Onken et al [22] had a similar setting, with the difference that instead of comparing various organic label types, they involved labels connected to more diverse production systems (e.g., natural, free-range, not GM fed).…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, twenty-nine of the examined studies applied this definition. Twenty-two of them (Studies 1 and 2 by Van Doorn and Verhoef [99]; Larceneux et al [8]; Bauer et al [100]; Schuldt and Hannahan [12], Stage 2; Ellison et al [101]; Gorissen and Weijters [85], Study 3; Prada et al [102], Experiments 1 and 2; Lee et al [103], Studies 1 and 2; Scholl-Grissemann [104], Studies 1 and 2; Amos et al [105], Study 1; Besson et al [56], Study 2; Küst [106]; Septianto et al [107], Study 1 and 2; Nadricka et al [108], Studies 1, 2, and 3; Parker et al [76], Study 1b) examined the effect of an organic label on hypothetical products (v HAO − v HB ), and six (Van Doorn and Verhoef [99], Study 3; Guilabert and Wood [132]; Hemmerling et al [127]; Laureati et al [128]; Kiss et al [133]; Apaolaza et al [126]) on organic products (v OAO − v OB ). One study (Johansson et al [130]) investigated the effect of a false organic label appearing on a conventional product (v CAO − v CB ).…”
mentioning
confidence: 99%
“…gluten-free ingredients) and ecological ethics (e.g. free-range grazing) (Parker et al, 2017). Verbeke et al (2013) claimed that credence-labels symbolize consumers' expectations of food quality and can be used by consumers to infer food quality.…”
Section: Theoretical Foundationmentioning
confidence: 99%